Social Media Analysis of Brand Awareness and Brand Image on Visitor Levels at Smart Fisheries Village (SFV) on Java Island - Dewi Alima Nostalia Suseno; Dimas Bayu Sasongko; Zayafika Mareta; Yernawilis Yernawilis; Normayasari Normayasari; Indah Alsita; Luchiandini Ika Pamaharyani (Dinasti International Journal of Education Management And Social Science, 2025)
The purpose of this study was to conduct a social media analysis of brand awareness and brand image on the number of visitors to the smart fisheries village (SFV) in Java Island. The method used in sampling is the convenience sampling method, namely a sampling technique based on the convenience of researchers with respondents who are met by chance, are considered suitable, and are willing to be data sources and meet the criteria determined by the researcher. Data analysis in this study used SPSS software by conducting correlation and linear regression tests. Based on the results of the analysis that has been done, the calculated r value for the relationship between X1 (social media) and Y (brand image) is 0.313, which is greater than the r table value of 0.173 and the calculated r value for the relationship between X2 (advertising) and Y (brand image) is 0.571, which is greater than the r table value of 0.173, so that both variables have a positive effect. The R-square value obtained is 0.873, which states that the social media and advertising variables have an effect on brand image of 87.30% and the remaining 12.70% is influenced by other variables.